Effectiveness of Online Learning Using Flipped Classroom Model Towards Mastery of Concepts and Students' Interpersonal Intelligence - Joni Albar; Sri Wardani; Sarwi Sarwi (International Conference on Science, Education, and Technology, 2021)
Interactive online learning with students first learns learning materials through the Flipped classroom learning model in learning to improve students' concept mastery skills and interpersonal intelligence in the online-based learning process. The purpose of this study measured the effectiveness of the Flipped classroom model towards the mastery of concepts and interpersonal intelligence of elementary school students. Quantitative research method type experimental quasi design with non-equivalent design one group pretest and posttest. The population of grade 5th students of SD Negeri 1, Research sample of 50 students. Research data collection techniques using test questions and questionnaires. Data analysis techniques use simultaneous test and t independent sample test. The results showed an f-test of 10.87 while the table was 4.99 and the T-test showed an at-count of 8.22 while 3.4. The results of the data analysis showed significant differences in the mastery of concepts and interpersonal intelligence by using flipped classroom models in the learning process. The conclusion of this study is that applying flipped classroom model in online learning is very effective in improving the mastery of concepts and interpersonal intelligence in elementary school students with students first learning the material before learning begins.